<span>hello :
</span>F(x) = (x-3) (x+8) (x-11)
F(x) =0
<span>x-3= 0 or x+8=0 or x-11 = 0
x=3 or x=-8 or x=11
</span><span>the zeros of the polynomialare : 3 , -8 , 11 </span><span>
</span>
Answer: 644,800
Step-by-step explanation:
This can also be solved using the terms of Arithmetic Progressions.
Let the 13 years be number of terms of the sequences (n)
Therefore ;
T₁₃ = a + ( n - 1 )d , where a = 310,000 and d = 9% of 310,000
9% of 310,000 = 9/100 x 310,000
= 27,900
so the common difference (d)
d = 27,900
Now substitute for the values in the formula above and calculate
T₁₃ = 310,000 + ( 13 - 1 ) x 27,900
= 310,000 + 12 x 27,900
= 310,000 + 334,800
= 644,800.
The population after 13 years = 644,800.
Answer:
4x-7y = -21
Step-by-step explanation:
1. Move 4/7x to the other side
-4/7x+y=-3
2. Multiply both sides by -7
4x-7y=-21
Answer: The b-value is the middle number, the number next to the X
Y = 8x + 29 is the answer for your question